Development of empathy to improve school environment (2019)
This research paper is aimed at determining the influence of empathy in building a healthy school environment to reduce violence in the classroom, by implementing teaching strategies. Through a qualitative approach and a participatory action research methodology, the problem was observed, a diagnosis was made and, with the study of theorists, a classroom strategy was generated focused on the development of empathy in the students. The results are positive because there is evidence of a decrease in verbal and physical abuse rates within the studied population. From this, it is concluded the importance of the implementation of these strategies in the study plans to improve the Synthetic Index of Educational Quality referring to the school environment.